The Impact of Socioeconomic Factors on Intermediaries in Illegal Migration (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the impact of social and economic factors on the exacerbation of the phenomenon of human smuggling intermediaries in the city of Zuwara. The study adopted a descriptive-analytical approach and a field survey method, applied to a purposive sample of the city's youth involved in smuggling networks. The data collection tools consisted of in-depth field interviews and a questionnaire, which were statistically analyzed using the SPSS software.The findings revealed that unemployment, financial difficulties, and the desire for quick financial gain constitute the most prominent economic motives for the respondents. Socially, the results indicated the influence of networks of friends and relatives working in the field, alongside exacerbated family disputes, coupled with a conditional family acceptance based on financial returns. Furthermore, the study demonstrated that tribal cohesion in the city generates a mechanism of "social concealment" that protects intermediaries and prevents reporting them, which has contributed to the formation of a subculture that supports this activity and adapts to its risks.
Keywords: Illegal Migration, Migration Intermediaries, Human Smuggling